Evaluation of the cost of using power plant reject heat in low-temperature district heating and cooling networks. (15th January 2016) - Colmenar-Santos, Antonio; Rosales-Asensio, Enrique; Borge-Diez, David; Collado-Fernández, Eduardo
Graphical abstract: Highlights: Costs of district heating schemes with different weather conditions are addressed. The implementation of district energy systems would greatly reduce CO2 emissions. From the quantitative evidence, net primary energy savings obtained are similar. Even having to transport heat over long distances, significant savings are achieved. In Southern Europe, district heating and cooling networks should be used together. Abstract: The purpose of this paper is to assess the economic impact following as a result of the conversion of conventional stations to cogeneration plants connected to a system for distributing heat and refrigeration. The analysis will be carried out through a financial evaluation in order to assess yearly variations of the whole scheme expenditure. In particular, yearly capital and operating costs of supplying cold and heat to urban areas that represent weather conditions in northern, central, and southern Europe (Oldenburg–Wilhelmshaven, Bristol, and Cartagena, respectively) were studied. In the base case scenario, today conditions are represented; they will be compared with alternative scenarios in which existing conventional thermal power stations will be converted into cogeneration plants.